Synthesis of azoarenes by reductive dimerization of nitroarenes using ammonium bromide and magnesium - Sridhara, Malavalli Basavaraju; Suhas, Ramesh; Gowda, Dase Gowda Channe (European Journal of Chemistry, 2013)
A simple and efficient protocol for the synthesis of symmetrically substituted azoarenes from nitroarenes by using ammonium bromide as hydrogen donor and magnesium powder as catalyst at room temperature in methanol media is described. Various azoarenes containing few additional substituents such as halogen, methyl, hydroxyl, methoxy, ethoxy etc. functions have been synthesized in a single step by the use of this reagent. The conversion is clean, rapid, chemo-selective and high yielding.